Pengaruh Overconfidence, Illusion of Control, dan Loss Aversion terhadap Keputusan Investasi Investor Gen Z - Putu Purnama Dewi; I Putu Agus Yudiantara (Juara: Jurnal Riset Akuntansi, 2026)
Investors take or make investment decisions based on their capital and information. These decisions can result from rational or irrational investor actions. This study aims to determine the effect of independent variables, namely overconfidence, illusion of control, and loss aversion on Gen Z investment decisions in the capital market. The approach used a quantitative method by taking a sample of 100 respondents using a purposive sampling technique. The data obtained will be tested using the SmartPLS application analysis approach. The results show that overconfidence has a positive and significant effect on Gen Z investment decisions in the capital market and loss aversion shows positive and significant results on Gen Z investment decisions in the capital market. Meanwhile, illusion of control has a negative and insignificant effect on Gen Z investment decisions in the capital market. Further research is expected to take a larger sample to expand the scope of the study.